2017
DOI: 10.1007/s11307-017-1091-9
|View full text |Cite|
|
Sign up to set email alerts
|

Repeatability of [68Ga]DKFZ11-PSMA PET Scans for Detecting Prostate-specific Membrane Antigen-positive Prostate Cancer

Abstract: Purpose We studied the effect of varying specific activity of [68Ga]DKFZ-PSMA11 ([68Ga]DP11) on repeated imaging of prostate-specific membrane antigen-positive (PSMA+) xenograft tumors. Procedures Athymic nude mice bearing PC3-PIP (PSMA+) and PC3 (PSMA−) bilateral flank tumors were assessed to study intra- and inter-day repeatability of [68Ga]DP11 imaging in mice administered [68Ga]DP11 or [67Ga]DP11 (as a dilution tracer) using imaging and biodistribution studies. Results Region-of-interest (ROI) analysis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 22 publications
3
3
0
Order By: Relevance
“…Thus, organ uptake data in small-animal 68 Ga-PSMA11 PET/ CT should be treated with caution. Our findings for interday reproducibility were consistent with previous studies on mice bearing PSMA 1/2 PC3 xenografts (20).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Thus, organ uptake data in small-animal 68 Ga-PSMA11 PET/ CT should be treated with caution. Our findings for interday reproducibility were consistent with previous studies on mice bearing PSMA 1/2 PC3 xenografts (20).…”
Section: Discussionsupporting
confidence: 92%
“…Likewise, the overall low PET signal (%IA/g) from the blood pool, liver, muscles, and background might have affected interreader and interday reproducibility for organ uptake. Both the high kidney uptake and the very low background, blood, liver, and muscle PET signals are in line with other studies reporting the biodistribution of 68 Ga-PSMA11 in mice (19,20). From day to day and reader to reader, regions of interest could not be placed identically; rather, there was a slight variation in location and, thus, in %IA/g readings.…”
Section: Discussionsupporting
confidence: 90%
“…We determined good repeatability for the tumor uptake of [ 18 F]­PSMA-1007 in xenograft mice between the scans from dynamic PET imaging, wCVs, RCs, and ICCs results obtained over two consecutive days. Our findings are comparable to those of previous studies on [ 68 Ga]­Ga-PSMA-11 and [ 68 Ga]­Ga-DP11 in PSMA-positive xenograft mice. , …”
Section: Discussionsupporting
confidence: 91%
“…Our findings are comparable to those of previous studies on [ 68 Ga]Ga-PSMA-11 and [ 68 Ga]Ga-DP11 in PSMA-positive xenograft mice. 44,45 Furthermore, we found that the inhibition of PSMA by 2-PMPA reduced the AUC of the TAC over 120 min by 37%. The 2-PMPA treatment altered k 2 and k 3 , but not K 1 ; the net influx rate constant K i and concentration in specific binding tissue (C S ) were also reduced in the inhibition group.…”
Section: ■ Resultsmentioning
confidence: 74%
“…The purified sample of 68 Ga showed only two peaks at 511 keV and 1077 keV. Several experiments were performed in mice to determine repeatability of the cyclotron-produced 68 Ga-HBED-CC, which are published in Molecular Imaging and Biology [12] .…”
Section: Methodsmentioning
confidence: 99%